The impact of land titling on labor allocation: Evidence from rural Peru - Nakasone, Eduardo (International Food Policy Research Institute, 2011)
This paper analyzes the relationship between land property rights and household labor allocation. It posits that land titling has two opposite effects on labor decisions. On one hand, enhancement of tenure security should lead to reductions in guarding requirements and to increases in the hours that households spend off their land (Field effect). On the other hand, decreases in the risk of expropriation should lead to higher parcel-attached investments and to higher labor productivity related to land (productivity effect). To investigate this hypothesis, a massive land titling program in rural Peru (the Special Program of Land Titling, or PETT) is analyzed. Propensity score matching estimations suggest that the productivity effect is much larger than the Field effect, leading to overall increases in household labor allocations to agricultural self-employed activities. These estimations are robust to different specifications within a cross-section and a four-round panel dataset.